Infection of rabbit T-cell and macrophage lines with human immunodeficiency virus. - Kulaga, H (1988)
We report the successful infection of two rabbit T-cell lines and one rabbit macrophage line with human immunodeficiency virus 1 (HIV-1). One T-cell line was a herpesvirus ateles transformant, the other T-cell line was a human T-cell leukemia virus I transformant, and the macrophage line was a simian virus 40 transformant. After infection with a high-titered HIV-1 stock, the rabbit cultures exhibited properties that closely mimic those of HIV-1-infected human cells. Productive infection was evident in cultures 7-14 days after infection, as shown by an increase in reverse transcriptase activity, a concomitant increase in positive cells detected by indirect immunofluorescence using serum from a patient with acquired immunodeficiency syndrome, and a decrease in cell viability. RNA gel blot hybridization and protein immunoblot analyses of infected cells indicated that all predicted viral transcripts and proteins were synthesized during the course of the infection. Proof that cell-free culture supernatants of the infected rabbit cell lines contained infectious virus was given by successful passage onto a susceptible human T-cell line. The ability of HIV-1 to infect transformed rabbit cell lines in vitro suggests that, with appropriate manipulation, the rabbit may provide a model for infection with HIV-1.